Penetration of a swallowed fish bone into pulmonary vein: diagnosis and management. Issue 11 (November 2020) - Akaishi, Tetsuya; Ishizawa, Kota; Fukutomi, Toshiaki; Yamamoto, Yasuchika; Ichikawa, Hirofumi; Watanabe, Suguru; Mori, Naoko; Saito, Mayuko; Takayama, Shin; Abe, Michiaki; Hatsugai, Kazuaki; Ishii, Tadashi
Abstract: We present a case of a 71-year-old woman who accidently swallowed a large fish bone that penetrated into the pulmonary vein. She visited the hospital the next day with a complaint of mild chest discomfort with slight pain and fever of 37.4 °C. Contrast-enhanced chest computed tomography (CT) scan revealed a large fish bone with a length of 35 mm impacted in the middle esophagus. The bone had penetrated into the pulmonary vein, causing mediastinitis. Blood tests revealed elevation in the white blood cell count and C-reactive protein level. Because intractable bleeding from pulmonary vein after endoscopic removal can be lethal, endoscopic removal of the fish bone in an operating room under general anesthesia with cardiovascular surgical standby for possible emergency surgery was selected. After endoscopic removal, mediastinal hematoma was absent with a follow-up chest CT scan, and the mediastinitis was treated with intravenous antibiotics. The patient shortly became afebrile with normalized blood test findings. After confirming the normal findings on the follow-up chest CT scan and endoscopic inspection in the next week, she was discharged from the hospital 10 days after hospitalization without any complications. When the swallowed bone penetrates into the major pericardial vessels, unprepared endoscopic removal may result in fatal sequelae such as intractable mediastinal hemorrhage. Urgent consultation with cardiovascular or thoracic surgeons for a possible emergent surgery is needed before endoscopic removal is attempted. Abstract : Medical imaging; Gastrointestinal system; Emergency medicine; Internal medicine; Radiology; Chest computed tomography, Endoscopic removal, Mediastinitis, Penetration, Pulmonary vein, Swallowed fish bone.